DIVERSITAS FORAMINIFERA BENTONIK KECIL DI DAERAH PERAIRAN SEMARANG (LEMBAR 1409) JAWA TENGAH - -, Lia Jurnaliah (Bulletin of Scientific Contribution, 2011)
Location of seafloor sediment is Semarang waters (sheet map of 1409), Central Java. Geographically, research area is in coordinate 109°30'-111°00' and 06°00' - 07°00'.Twenty samples of two phi seafloor sediment were examined in order to know diversity of small benthic foraminifera. Based on quantitative analysis, small benthic foraminifera are composed of 7 Order, 27 Families, 38 Genus, 57 Species, and 235889 Specimen. The calculation of index diversity are shown between 0,3 - 1,